PENGARUH ARUS KAS DAN PERPUTARAN MODAL KERJA TERHADAP LIKUIDITAS PERUSAHAAN - FATMAWATI SHOLICHAH (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2020)
The purpose of this research; 1) to identify and analyze cash flow and working capital turnover variables which have a partial effect on liquidity; 2) to identify and analyze working capital turnover variables which have partial effect on liquidity; 3) to identify and analyze cash flow and working capital turnover variables that simultaneously influence the liquidity of the Company. The sampling technique was done by using purposive sampling method with certain criteria (researchers). Methods of data analysis using multiple regression analysis techniques. Based on the results of the research analysis, it can be seen that 1) cash flow and working capital turnover have a partial effect on liquidity in telecommunications companies listed on the Indonesia Stock Exchange in 2010-2017, 2) Cash flow and working capital turnover simultaneously affect liquidity in the Company 3 ) Cash flow has a dominant effect on liquidity at Telecommunication Companies.